Study on the logic and effectiveness of crisis learning in the promotion policy adjustment: an observation based on the adjustment of COVID-19 prevention policy in China - Wei, Changwei; Xu, Jiaxi; Xu, Zuying (Frontiers in Public Health, 2024)
Background: As the impact of COVID-19 on normal production and living conditions diminishes, this serious emergency is come to an end. China's policy framework has facilitated positive adjustment over the past three years by timely modifying its emergency response to changes in viruses and epidemics. This paper aims to explore the logic of China's policy framework that promoted policy adjustment through crisis learning during COVID-19. Methods: By gathering and classifying China's epidemic prevention policies throughout the past three years, integrating policy texts, and analyzing key events, this article examines the process of supporting policy adjustment through crisis learning in the policy system during COVID-19. Results: The Chinese government's COVID-19 policy adjustment process can be divided into four stages, namely the "Stress response period", the "COVID-19 prevention and control period", the "Regular prevention and control period", and the "Overall adjustment period". The policy adjustments in each stage demonstrate the logic and effectiveness of crisis learning in the promotion policy adjustment. The study has determined that the motivational logic comprises three crucial elements: security requirements, accountability pressure, and reputation management. The institutional logic encompasses both the organizational and resourceful environments, and the institutional and cultural environment. Additionally, the behavioral logic of policy adaptation aligns with the strategy of crisis learning. Meanwhile, the logical framework of 'crisis learning-policy adjustment' can be verified using the Chinese government's policy adjustment in COVID-19 as an example. Conclusion: Establishing an effective post-crisis learning system is crucial to improving the effectiveness of crisis response. There is a logical link between crisis learning and policy adjustment. The implementation of policy adjustment needs to be based on the results of crisis learning. Government departments are essential for crisis learning and policy adjustment.